A Study to Assess the Effectiveness of Mentha Bar in Reduction of Dysmenorrhea among Adolescent Girls in Selected College, Hyderabad - Daniel Sharon, Kalla (International Journal of Nursing and Medical Investigation, 2024)
Background: Dysmenorrhea is characterized by intense uterine discomfort that radiates to the back and legs and occurs during menstruation. In medical interviews, women frequently fail to mention that they suffer from dysmenorrhea. Herbal supplements have been shown to be an exceptionally effective treatment option for menstrual issues. One of the most significant benefits of using herbal remedies is that they provide results for a long time without having any side effects for the consumer. Mint is a soothing plant that can be used without worry despite its invasive nature and propensity to spread. Its most common use includes providing relief from the discomfort associated with indigestion, cramps, menstrual cramps, flatulence, upset stomach, nausea, and vomiting as well as child colic. Method: Quantitative evaluative research approach and Quasi experimental research design were used. The study was conducted in the Swapna School of Nursing, Chaitanyapuri, Hyderabad, and Vijay Marie College of Nursing Begumpet, Hyderabad. Adolescent girls with dysmenorrhea who were studying in the Swapna School of Nursing, Chaitanyapuri, Hyderabad, and Vijay Marie College of Nursing Begumpet, Hyderabad, were selected as a sample size. Purposive sampling technique was used in this study. Results: The calculated paired t-test calculated value for experimental group is 5.9 and table value is 2.04 at 0.05% level of significance and 29 degree of freedom; hence, the calculated “t” value is greater than table value, indicating that the null hypothesis (H0 ) is rejected and research hypothesis (H1 ) is accepted. Conclusion: The study found that adolescents with dysmenorrhea who experienced major side effects responded favorably to the efficacy and pain reduction of the medication.